IoT 네트워크 상의 머신러닝 기반 DoS 및 DRDoS 탐지연구 - 여승연(Seung-Yeon Yeo); 조소영(So-Young Jo); 김지연(Jiyeon Kim) (한국컴퓨터정보학회논문지, 2022)
본 논문은 다수의 사물인터넷 단말에서 보편적으로 수집할 수 있는 시스템 및 네트워크 메트릭을학습하여 각 사물의 경험데이터를 기반으로 서비스거부 및 분산반사 서비스거부 공격을 탐지하는침입 탐지 모델을 제안한다. 먼저, 공격 시나리오 유형별로 각 사물에서 37종의 시스템 및 네트워크메트릭을 수집하고, 이를 6개 유형의 머신러닝 모델을 기반으로 학습하여 사물인터넷 공격 탐지 및분류에 가장 효과적인 모델 및 메트릭을 분석한다. 본 논문의 실험을 통해, 랜덤 포레스트 모델이96% 이상의 정확도로 가장 높은 공격 탐지 및 분류 성능을 보이는 것을 확인하였고, 그 다음으로는K-최근접 이웃 모델과 결정트리 모델의 성능이 우수한 것을 확인하였다. 37종의 메트릭 중에는 모든공격 시나리오에서 공격의 특징을 가장 잘 반영하는 CPU, 메모리, 네트워크 메트릭 5종을 발견하였으며 큰 사이즈의 패킷보다는 빠른 전송속도를 갖는 패킷이 사물인터넷 네트워크에서 서비스거부및 분산반사 서비스거부 공격 특징을 더욱 명확히 나타내는 것을 실험을 통해 확인하였다. We propose an intrusion detection model that detects denial-of-service(DoS) and distributed reflection denial-of-service(DRDoS) attacks, based on the empirical data of each internet of things(IoT) device by training system and network metrics that can be commonly collected from various IoT devices. First, we collect 37 system and network metrics from each IoT device considering IoT attack scenarios; further, we train them using six types of machine learning models to identify the most effective machine learning models as well as important metrics in detecting and distinguishing IoT attacks. Our experimental results show that the Random Forest model has the best performance with accuracy of over 96%, followed by the K-Nearest Neighbor model and Decision Tree model. Of the 37 metrics, we identified five types of CPU, memory, and network metrics that best imply the characteristics of the attacks in all the experimental scenarios. Furthermore, we found out that packets with higher transmission speeds than larger size packets represent the characteristics of DoS and DRDoS attacks more clearly in IoT networks. KCI Citation Count: 0